Calreticulin and PDIA3, two markers of endoplasmic reticulum stress, are associated with metabolic alterations and insulin resistance in pediatric obesity: A pilot study - Antoniotti, Valentina; Bellone, Simonetta; Gonçalves Correia, Filipa Patricia; Peri, Caterina; Tini, Sabrina; Ricotti, Roberta; Mancioppi, Valentina; Gagliardi, Mara; Spadaccini, Daniele; Caputo, Marina; Corazzari, Marco; Prodam, Flavia (Frontiers in Endocrinology, 2022)
Our aim was to evaluate the markers of endoplasmic reticulum (ER) stress among children and adolescents with obesity in relation to metabolic alterations. Calreticulin (CALR) and PDIA3 circulating levels were assessed on 52 pediatric subjects, 26 patients with obesity and 26 normal weight controls (4-18 years) enrolled in a pilot study. Clinical and metabolic evaluations were performed (BMI-SDS, insulin, and glucose at fasting and during an oral glucose tolerance test, lipid profile, blood pressure), and metabolic syndrome was detected. PDIA3 was higher (p<0.02) and CALR slightly higher in children with obesity than in controls. PDIA3 was related positively to Tanner stages. Both PDIA3 and CALR were positively associated with insulin resistance, cholesterol, and triglycerides and the number of criteria identifying metabolic syndrome, and negatively with fasting and post-challenge insulin sensitivity. Our preliminary findings suggest the existence of a link between ER stress and metabolic changes behind obesity complications even in pediatric age. CALR and PDIA3 could be early markers of insulin resistance and dyslipidemia-related ER stress useful to stratify patients at high risk of further complications.